2007
DOI: 10.1289/ehp.10249
|View full text |Cite
|
Sign up to set email alerts
|

The Contribution of Dental Amalgam to Urinary Mercury Excretion in Children

Abstract: BackgroundUrinary mercury concentrations are widely used as a measure of mercury exposure from dental amalgam fillings. No studies have evaluated the relationship of these measures in a longitudinal context in children.ObjectiveWe evaluated urinary mercury in children 8–18 years of age in relation to number of amalgam surfaces and time since placement over a 7-year course of amalgam treatment.MethodsFive hundred seven children, 8–10 years of age at baseline, participated in a clinical trial to evaluate the neu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
68
2
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(79 citation statements)
references
References 45 publications
4
68
2
2
Order By: Relevance
“…This finding suggests that Hg toxicity is nonlinear and that chronic Hg exposure may impair excretion and increase retention. Based on the preceding findings, the study's boys retained and accumulated significantly higher levels of Hg than the study's girls over the course of comparable Hg exposures from Hg-amalgam dental fillings (Woods et al 2007). …”
Section: Mercury (Hg)mentioning
confidence: 84%
See 2 more Smart Citations
“…This finding suggests that Hg toxicity is nonlinear and that chronic Hg exposure may impair excretion and increase retention. Based on the preceding findings, the study's boys retained and accumulated significantly higher levels of Hg than the study's girls over the course of comparable Hg exposures from Hg-amalgam dental fillings (Woods et al 2007). …”
Section: Mercury (Hg)mentioning
confidence: 84%
“…Woods et al (2007) found that mean urinary Hg excretion for boys and girls were similar at baseline. However, at about two years after amalgam placement, urinary Hg excretion declined for both genders.…”
Section: Mercury (Hg)mentioning
confidence: 87%
See 1 more Smart Citation
“…This procedure was applied both to baby teeth and adult teeth b Includes only subjects assigned to the dental amalgam group number of amalgam restorations had a significant dose-response relationship with Hg urine levels. Likewise, Woods et al (2007), in a longitudinal study in children, found urinary Hg concentrations were highly correlated with the number of amalgam fillings. Post-mortem studies also show this same dose-dependent central theme.…”
Section: Discussionmentioning
confidence: 92%
“…The authors conclude that the integrated daily mercury dose of 7.4 µg for a high amalgam load is well below the tolerable dose of 30 µg (WHO 2003, ATSDR 1999. A recent paper indicated that there may be difference in mercury excretion between boys and girls 8-18 years of age, treated with dental amalgam (Woods 2007).…”
Section: Exposure To Mercury In Adultsmentioning
confidence: 99%